Variation in morpho-physiological characters and yield components of summer mungbean (Vigna Radiata(L.) wilczke) varieties - Alam Mondal, Mohd Monjurul; Malek, M. A.; Puteh, Adam (Bangladesh Botanical Society, 2015)
Twelve modern summer mungbean cultivars were evaluated to assess morpho-physiological characters, yield attributes and seed yield. Results revealed that high yielding cultivars, in general, showed superiority in morpho-physiological characters and seed yield/plant than the low yielding cultivars. However, in case of unit area basis, result revealed that seed yield/ha was greater in low yielding cultivars than the high yielding ones, yet they produced lower seed yield/plant compared to high yielding ones due to increase number of plants per unit area and these low yielding cultivars also matured 10 - 15 days earlier than high yielders. Among the cultivars, BINAmung-5 produced the highest seed yield/ha (1711 kg/ha) with lower HI (20.0%) and took longer days to maturity (69 days). On the other hand, BARImung-6 showed second highest seed yield (1697 kg/ha) with highest HI (32.6%) and matured earliest, took 60 days after sowing that might be fit the existing cropping pattern in Bangladesh.